Fluorescence in Bulimulus Inscendens Binney - Hugh C. Rawls; John M. Baum; Roger L. Yates (Hello World!, 1972)
Fluorescence under ultraviolet lighthas been reported by several authors to occur in the mucus of certain land snails. We now wish to report the discovery of fluorescence in the mucus of specimens of Bulimulus inscendens Binney and to relate the phenomenon in this species to the presence of a bacterial pigment.